PENGAMBILKIRAAN FIQH REALITI (WAQI’) DALAM PENENTUAN HUKUM ISLAM KONTEMPORARI: ANALISIS PENDEKATAN SHAYKH ABDULLAH BEN BAYYAH - Zulkarnain, Saiful Islam Nor Mohd; Ramli, Mohd Anuar (Jurnal ’Ulwan, 2024)
Nass syara’ and the human condition have a very close relationship. This is because nass syara’ is the core of religion that is the guide, while the current human reality is the field for the implementation of the guide. The clash between the hardline (tashaddud) who are too attached to the source of the text without celebrating the local reality and the group who take it easy (tasahul) who leave the source of sharia holding has created religious conflict in society. Thus, the combination between the demands of Shariah idealism and the current and local reality taking into account is able to synergize Islamic law as a guide for life. Accordingly, this study will focus on the analysis of the approach of fiqh al-waqi ‘which was parsed by Shaykh‘ Abdullah Bin Bayyah through his work Tanbih al-Maraji ‘‘ Ala Ta’sil Fiqh al-Waqi ’. To achieve these objectives, this qualitative study applies the library approach fully by analyzing the content of the work. The results of the study found that Shaykh ‘Abdullah Bin Bayyah was a leading Islamic scholar in the field of usul al-fiqh and fiqh. The idea of Fiqh al-Waqi ‘that is preached is not a call to abandon the Islamic text or to submit to the pressures of reality, in fact he stressed that the assessment of a local reality must be through the legal methodology outlined. For example, in dealing with the polemic of the implementation of hudud law in Islamic countries, Shaykh ‘Abdullah Bin Bayyah first divides the position of hudud law in religion, which is from the aspect of recognition of his duty as a matter of faith, while in terms of its implementation is a matter of worship. The debate outlined focuses on the context of the current place to implement hudud punishment whether within the jurisdiction and ability to implement or not which leads to the postponement of the hudud law.